PENGALAMAN SELF-CARE BERDASARKAN TEORI OREM PADA PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Kiki Wahyuni; Wahyu Hidayati (Jurnal Keperawatan Diponegoro, 2012)
Hemodialysis patients generally have a complex problem and require a holistic fulfillment of needs. It is closely related to the motivation and self-care abilities of chronic kidney disease patients to maintain an optimal quality of life.The purpose of this study was to describe the self-care application of hemodialysis patients. This study used a qualitative research design with a phenomenological approach.  Five informants chosen through inclusion criteria were interviewed using in depth interview with semi-structure design. The result showed good understanding of the informants about chronic kidney disease undergoing hemodialysis through an understanding of the history of past experience. Coping mechanisms to minimize the occurrence of informants do self-care deficit and efforts in meeting the needs of hemodialysis patients and optimization of different body condition. Informants showed different ways to do coping mechanism to minimize self care deficit; to meet their needs and to optimize their body condition. The analysis of informants’ experience is necessary in order to control the enabling and inhibiting factors of body condition. Hemodialysis patients are expected to meet the need of self-care by having discipline to control fluids and nutrients balance in the body